SLANG LANGUANGE AND THE DAILY LIFE OF TWITTER USERS - Ramadani, Multiara; Nur, Sahril; Sunra, La (Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
Slang language is a style of language that consists of phrases and terms that are considered to be very casual, it is more popular in written speech and is usually limited to a certain setting or group of individuals. The aims at this study are to investigate the types of slang language used in twitter and to explore the reasons for people using slang language in their daily life. The data in this study is qualitative data was taken based on Twitter accounts: Pop Base (@PopBase) and Chart Data (@chartdata) that become a place for conveying information about music industry in real time. In this study I found 53 comments which consisted of slang. The slang analysis is divided into five aspects: types of slang, meaning of slang, types of slang based on Allan and Burridge's theory (2006), function of slang based on Allan and Burridge's theory (2006) and the reason people use slang in their daily life. From the acronym slang type there are 28 data, then for imitative there are 3 data, then there are 5 data which is flippant slang types, then 7 data which is clipping slang types, and finally there are 10 data which is fresh and creative slang types. From 14 reasons people use slang in their daily life, this study found there were 8 reasons of using slang in the data, there are: 5 data which is casual conversations, then 26 data which is messaging and social media, then 6 data by expressing emotions, then there are 2 data by describing trends and pop culture, then nicknames and pet names only found 1 data, next there are 6 data by creating catchphrases, then 1 data using social media and internet memes, and finally there are 5 data by easing communication in specific situations.